The collected writings of Sherman and Grace Coolidge - Coolidge, Sherman; Coolidge, Grace (University of Nebraska Press, 2023)
Tadeusz Lewandowski presents the articles, stories, speeches, dispatches, letters, poems, and statements of Arapaho advocate Sherman Coolidge and his New York City society wife, Grace Wetherbee Coolidge.